Fatores de risco para sobrepeso em crianças no Sul do Brasil Risk factors for overweight in children from Southern Brazil - Maria de Lourdes Drachler; Simone Pont Zambonato Macluf; José Carlos de Carvalho Leite; Denise Rangel Ganzo de Castro Aerts; Elsa Regina Justo Giugliani; Bernardo Lessa Horta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
Estudo transversal de base populacional investigou determinantes de sobrepeso em crianças de 12 a 59 meses em Porto Alegre (n = 2.660). Razões de chance (RC) de sobrepeso, definido por peso/altura > 2 escores-z do padrão NCHS, foram estimadas para condições sócio-econômicas e demográficas, ambiente social imediato e eventos de saúde da criança. A prevalência de sobrepeso foi 6,5%. No modelo multivariado, a chance de sobrepeso na criança associou-se positivamente à escolaridade materna (escolaridade > 12 anos, RC = 2,36; IC95%: 1,21-4,60; 9-11 anos, RC = 2,07; IC95%: 1,16-3,70) e à renda familiar per capita > 2 salários mínimos (RC = 1,86; IC95%: 1,13-3,08) e negativamente ao trabalho materno remunerado (RC = 0,72; IC95%: 0,52-0,99). A chance foi maior para os nascidos grandes para idade gestacional (RC = 2,29; IC95%: 1,36-3,85) e menor para os nascidos pequenos (RC = 0,57; IC95%: 0,33-0,99), comparados aos nascidos com peso adequado. Escolaridade paterna, qualificação profissional dos pais e idade materna ao nascimento da criança evidenciaram efeito somente no modelo bruto. São necessários programas para prevenir sobrepeso em crianças, com especial atenção às famílias e crianças em maior risco. Risk factors for overweight were investigated in a cross-sectional survey of children aged 12-59 months in the Southern Brazilian city of Porto Alegre (n = 2,660). Odds ratios (OR) for overweight, defined by weight/height > 2 z-scores of the NCHS standards, were estimated for socioeconomic and demographic conditions, social environment, and childhood health events. Prevalence of overweight was 6.5%. In the multivariate model, the odds of overweight were positively associated with maternal education (schooling > 12 years, OR = 2.36; 95%CI: 1.21-4.60; 9-11 years, OR = 2.07; 95%CI: 1.16-3.70) and family income per capita > 2 times the minimum wage (OR = 1.86; 95%CI: 1.13-3.08) and negatively associated with maternal work (OR = 0.72; 95%CI: 0.52-0.99). Odds were higher for children born large-for-gestational-age (OR = 2.29; 95%CI: 1.36-3.85) and lower for children born small (OR = 0.57; 95%CI: 0.33-0.99), as compared to those born with adequate birth weight for gestational age. Paternal schooling, parental occupation, and maternal age at the child's birth were associated with overweight in the unadjusted model only. Programs are needed to prevent overweight during childhood, with special attention to families and children at increased risk.